Analyzing the Relationship Between Preventative Healthcare Utilization and Higher Education Levels in Underserved Los Angeles Communities - Elhaija, Ahmad; Ravi, Harshita (International Journal of Medical Students, 2025)
BACKGROUND: Despite significant advancements in scientific research to reduce the risk of various illnesses and health conditions, the underutilization of preventive healthcare poses a significant barrier to enhancing public health outcomes.1 A 2020 study found that only 8% of Americans undergo routine preventive care screenings2; racial minorities such as Hispanic Americans are even less likely to receive preventive health services due to socioeconomic disparities.3 Individuals with higher educational attainment are more likely to receive routine health checkups4, and have higher vaccination rates.5 To illustrate these dynamics, this case focuses on Maywood and Bell, two adjacent cities with large patient populations from immigrant and refugee backgrounds. Educational attainment rates, which represent the percentage of residents with at least a bachelor’s degree level of education, are notably lower in Maywood and Bell (8.7% and 8.8%) compared to California as a whole (37.0%). The percentage of residents without health coverage in Maywood and Bell (18.0% and 13.9%, respectively) are higher than California’s average of 6.5%.6,7 THE CASE: This case was conducted by The International Healthcare Organization (IHO), a 501(c)-3 nonprofit composed of doctors, nurses, medical students, non-profit advisors, and healthcare administrators.8 IHO team members conducted a convenience sample of adult community members from Maywood and Bell during a mobile community health clinic event. 120 adult respondents were given a survey to complete anonymously. All participants provided informed consent. The survey contained questions pertaining to respondents’ educational attainment and whether they had received various medical examinations during the year. Respondents completed the survey by selecting one of the following options, depending on the question: yes/no; numerical response; age range; frequency range; 5-point Likert scale. Table 1 reveals substantial disparities across three main areas: vaccinations, routine medical examinations, and female-specific cancer screenings. Rates of vaccination uptake differed greatly between college-educated and non-college-educated groups: 68.8% of college-educated individuals receiving a COVID-19 vaccination, whereas only 56.8% of their non-college-educated counterparts indicated the same. Disparities were also evident in dental and blood examinations, participants with a college education were over 10% more likely to have had at least one blood or dental examination within the year. Finally, a sizable gap was observed in the category of female-specific screenings. Only 11.1% of college-educated women reported receiving both a pap smear and mammogram test, whereas none of the non-college-educated women respondents reported receiving either screening. CONCLUSION: The findings of the survey, as well as results from other literature, underscore how educational attainment not only influences preventative care usage but could also potentially be the driving factor behind it. Tertiary education teaches individuals the importance of preventive health practices, leading to higher health status and overall health awareness,9 but also leads to significantly higher risk perception in comparison to their less educated counterparts. Current literature and this study emphasize the need for targeted interventions to ensure equitable healthcare access and utilization. Education greatly enhances public health outcomes10, suggesting that future interventions should prioritize addressing educational disparities.